Direct visualization of transcription-replication conflicts reveals post-replicative DNA:RNA hybrids - Stoy, Henriette; Zwicky, Katharina; Kuster, Danina; Lang, Kevin S; Krietsch, Jana; Crossley, Magdalena P.; Schmid, Jonas A.; Cimprich, Karlene A.; Merrikh, Houra; Lopes, Massimo (Nature structural & molecular biology, 2023)
Transcription-replication collisions (TRCs) are crucial determinants of genome instability. R-loops were linked to head-on TRCs and proposed to obstruct replication fork progression. The underlying mechanisms, however, remained elusive due to the lack of direct visualization and of non-ambiguous research tools. Here, we ascertained the stability of estrogen-induced R-loops on the human genome, visualized them directly by electron microscopy (EM), and measured R-loop frequency and size at the single-molecule level. Combining EM and immuno-labeling on locus-specific head-on TRCs in bacteria, we observed the frequent accumulation of DNA:RNA hybrids behind replication forks. These post-replicative structures are linked to fork slowing and reversal across conflict regions and are distinct from physiological DNA:RNA hybrids at Okazaki fragments. Comet assays on nascent DNA revealed a marked delay in nascent DNA maturation in multiple conditions previously linked to R-loop accumulation. Altogether, our findings suggest that TRC-associated replication interference entails transactions that follow initial R-loop bypass by the replication fork. The authors develop an EM-based method to directly visualize R-loops. Applying this method to transcription-replication conflicts in human and bacterial cells, they show that DNA:RNA hybrids accumulate primarily behind replication forks, and are linked to fork slowing and fork reversal.